PENDAMPINGAN PENGOLAHAN KRIPIK GEDEBOG PISANG“KRIPBOGPIS” DAN ASPEK LEGALITAS DI DESA CILELES KABUPATEN LEBAK - Saepudin, Eli Apud; Kamilah, Fithrotul; Handayani, Putri; Amilia, Rizki; Wahyiah, Ita Rosita; Hifni, Mohammad (Jurnal Akselerasi Merdeka Belajar dalam Pengabdian Orientasi Masyarakat (AMPOEN): Jurnal Pengabdian kepada Masyarakat, 2024)
The farmer group community in cisalak village, cileles district, lebak planted 2000 banana trees in 12 hectares and the banana harvest period in one year was 2 harvests but left banana stems which could only be used as compost by chopping them finely and letting them dry out the problem faced by farmers when harvesting banana stems had no selling value after Bina Bangsa University lecturers carried out PKM mentoring activities, the results of the assistance could utilize banana gedegogs into delicious chips. savory, nutritious, added using a variety of flavors and, the brand given is Kripbogpis banana gedebog chips where these chips can be a regional superior product if they are well managed, the brand is given is Kripbogpis, savory, nutritious in addition to using a variety of flavors and, the brand given is Kripbogpis banana gedebog chips where these chips can become regional superior products if they are well managed, packaging, brands registered with the Ministry of Law and Human Rights have legality will definitely have a characteristic of the product so that the community can benefit a lot.